RELATIONS BETWEEN THE HAN DYNASTY AND THE USUN STATE (Journal of history, 2025)
The relations between the Han Dynasty and the Usun State constitute one of the historical phenomena that laid the foundation for the formation and development of the Silk Road. These ties served as a driving force for trade and cultural exchange between East and West, ensuring regional security and transit stability in Central Asia. From the perspective of studying Eurasian economic and cultural integration today, examining this historical experience is highly relevant as it demonstrates an early model of intergovernmental partnership and interdependence mechanisms. The main objective of the study is to comprehensively analyze the political, economic, and cultural relations between the Han Dynasty and the Usun State and to identify their contribution to the formation and development of the Silk Road. The research also aims to show the impact of the Han Empire’s economic expansion and the Usun State’s geopolitical position on the security of trade routes and cultural exchange. This study is based on qualitative and historical-comparative methods. Primary sources—ancient Chinese chronicles and archaeological materials—were systematized and processed through content analysis. The political structures, diplomatic missions, economic and cultural relations of the Han Dynasty and the Usun State were analyzed using comparative tables. The historical-geographical approach made it possible to identify the main routes of the Silk Road, their transit significance, and security factors. The results showed that the relations between the Han Dynasty and the Usun State directly influenced the formation and stability of the Silk Road. Diplomatic missions led by Zhang Qian determined the military power and geopolitical role of the Usun State, strengthening strategic partnership between the two countries. Marriage alliances and coalition mechanisms weakened the Xiongnu expansion and ensured the security of trade routes. In addition, the study demonstrated that, along with goods, religions, ideas, technologies, and plant species also circulated along the Silk Road, reinforcing cultural integration between civilizations.
Keywords: Han Dynasty, Usun State, Silk Road, political relations, economic expansion